Alocação de antenas para rede celular de 4G utilizando algoritmos meméticos - Costa, Vinícius Oliveira (Universidade Federal do Tocantins, 2018)
This work deals with the issue of radio base stations (RBSs) allocation for the 4G cell phone system, which in Brazil uses the LTE (Long Term Evolution) protocol. Such problem consists in a certain geographical region, where potential customers might be found, having antennas to cover the largest possible area of the region under study, taking into account the capacity of each antenna to serve customers with quality of service. The presented algorithm calculates the range of the RBS station, the minimum amount of necessary RBS to cover the area under study and the location of each RBS. In order to the algorithm to be developed the LTE communication system was investigated, signal propagation models beyond memetic algorithm, since the RBS allocation is a NP-hard problem. For the cell’s range of action it was considered, besides the model of propagation, the link budget calculation, throughput and noise signal relation. Therefore, a comparison between LTE operating on 700 MHz and 2,5 GHz frequencies was made. The RBS allocation algorithm was efficient covering more than 80% of the study area in 29 from the 30 analyzed cases. In relation to the frequency, LTE was considered more adequate operating on 700 MHz, for the quantity of RBS to cover the study area is smaller, if compared to 2,5 GHz frequencies.